Alkaloids - secrets of life : alkaloid chemistry, biological significance, applications and ecological role - Aniszewski, Tadeusz; ScienceDirect eBooks (Amsterdam ; Oxford : Elsevier, 2007)
Alkaloids, represent a group of interesting and complex chemical compounds, produced by the secondary metabolism of living organisms in different biotopes. They are relatively common chemicals in all kingdoms of living organisms in all environments. Two hundred years of scientific research has still not fully explained the connections between alkaloids and life. Alkaloids-Chemistry, Biological Significance, Applications and Ecological Role provides knowledge on structural typology, biosynthesis and metabolism in relation to recent research work on alkaloids. Considering an organic chemistry approach to alkaloids using biological and ecological explanation. Within the book several questions that persist in this field of research are approached as are some unresearched areas. The book provides beneficial text for an academic and professional audience and serves as a source of knowledge for anyone who is interested in the fascinating subject of alkaloids. Each chapter features an abstract. Appendices are included, as are a listing of alkaloids, plants containing alkaloids and some basic protocols of alkaloid analysis. * Presents the ecological role of alkaloids in nature and ecosystems * Interdisciplinary and reader friendly approach * Up-to-date knowledge.
Chapter 1. Definition, Typology and Occurrence -- of Alkaloids -- 1. Definition -- 2. Occurrence in nature -- Chapter 2. Alkaloid Chemistry -- 1. Alkaloids as secondary metabolism molecules -- 2. Synthesis and metabolism -- Chapter 3. Biological Significance of Alkaloids -- 1. Alkaloids in biology -- 2. Bioactivity -- 3. Biotoxicity -- 4. Narcotics -- 5. Alkaloids in the immune system -- 6. Genetic approach to alkaloids -- 7. Alkaloids in the evolution of organisms -- Chapter 4. Applications -- 1. Medicinal applications -- 2. Alkaloids as drugs -- 3. Agricultural applications -- 4. Biotechnology -- Chapter 5. Ecological Role of Alkaloids -- 1. Animal sequestration of alkaloids -- 2. Sexual behaviour -- 3. Feeding atractance and deterrence -- 4. A case study: Alkaloids and plant population changes.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Alkaloids; SCIENCE -- Chemistry -- Organic; Alkaloids; Electronic books